Effect of Pectin from Watermelon Rind on Quality of Roselle (Hibiscus sabdariffa L.) Jam - Lichanporn, Intira; Nanthachai, Nanchanok; Tanganurat, Palida; Singkhum, Auchalin; Kromnongpai, Pradit (Journal of Applied Research on Science and Technology (JARST), 2020)
This research aimed to determine the chemical and physical properties of pectin from watermelon rind and applied the extracted pectin for roselle jam production. The white and green parts of watermelon rind were boiled, dried (60 °C, 15 hours), and extracted by using 0.05 M hydrochloric acid and distilled water at 90 °C with an extraction time of 60 min. The results showed that the optimal extraction method to extract pectin from watermelon rind was hydrochloric acid extraction because of the moisture, ash, methoxyl content and degree of esterification (%DE) of extracted pectin were the most similar to the commercial pectin. The obtained pectin can be categorized as high methoxyl pectin (HMP). The extracted pectin was applied to the roselle jam product. The concentration of pectin from watermelon rind was varied at 0.10, 0.49, and 0.89 %, compared with commercial pectin (0.49 %). Results showed that roselle jam added with the watermelon pectin and control were not significantly different in color, total soluble solid, pH, and titratable acidity. All treatments showed that L*, a*, and b* values were in the ranges of 20.97-21.80, 0.37-0.77 and 2.27-2.90, respectively. Sensory evaluation of appearance, color, odor, taste, texture, and overall acceptance results indicated that roselle jam added with the watermelon pectin and control were not significantly different. However, results indicated that the jam with 0.89 % watermelon rind pectin had a high overall acceptance which was not different from the commercial pectin. Therefore, pectin from watermelon rind could potentially be used for replacement of the commercial pectin in the food industry.